I Don't Think the a Should be There

Calculus Level 5

x = 1 log 33 ( ( x + a 1 ) ( x + a + 1 ) ( x + a 3 ) ( x + a + 3 ) ) = 1 \displaystyle \sum_{x=1}^{\infty} \displaystyle \log_{33}\left(\frac{(x+a-1)(x+a+1)}{(x+a-3)(x+a+3)}\right)=1

If the sum of all possible real values of constant a a such that the infinite sum above is fulfilled can be represented as p q \frac{p}{q} for coprime positive integers p , q p,q , find p + q p+q .


Try the harder (way harder) version here .

Try the easier version here .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
May 10, 2015

x = 1 log 33 ( ( x + a 1 ) ( x + a + 1 ) ( x + a 3 ) ( x + a + 3 ) ) = log 33 ( ( a ) ( a + 2 ) ( a 2 ) ( a + 4 ) × ( a + 1 ) ( a + 3 ) ( a 1 ) ( a + 5 ) × ( a + 2 ) ( a + 4 ) ( a ) ( a + 6 ) × ( a + 3 ) ( a + 5 ) ( a + 1 ) ( a + 7 ) × ( a + 4 ) ( a + 6 ) ( a + 2 ) ( a + 8 ) × ( a + 5 ) ( a + 7 ) ( a + 3 ) ( a + 9 ) × . . . ) = log 33 ( ( a + 2 ) ( a + 3 ) ( a 2 ) ( a 1 ) ) = 1 ( ( a + 2 ) ( a + 3 ) ( a 2 ) ( a 1 ) ) = 33 a 2 + 5 a + 6 = 33 ( a 2 3 a + 2 ) a 2 + 5 a + 6 = 33 a 2 99 a + 66 32 a 2 104 a + 60 = 0 8 a 2 26 a + 15 = 0 ( 2 a 5 ) ( 4 a 3 ) = 0 { a = 5 2 a = 3 4 unacceptable, ln ( a 1 ) and ln ( a 2 ) are undefined \displaystyle \sum_{x=1}^\infty {\log_{33} \left(\frac{(x+a-1)(x+a+1)}{(x+a-3)(x+a+3)} \right)} \\ = \log_{33} {\left(\dfrac{\color{#D61F06}{(a)}(a+2)}{(a-2)\color{#3D99F6}{(a+4)}} \times \dfrac{\color{#D61F06}{(a+1)}(a+3)}{(a-1)\color{#3D99F6}{(a+5)}} \times \dfrac{\color{#D61F06}{(a+2)}\color{#3D99F6}{(a+4)}}{\color{#D61F06}{(a)}\color{#3D99F6}{(a+6)}} \\ \quad \quad \quad \quad \quad \times \dfrac{\color{#D61F06}{(a+3)}\color{#3D99F6}{(a+5)}}{\color{#D61F06}{(a+1)}\color{#3D99F6}{(a+7)}} \times \dfrac{\color{#D61F06}{(a+4)}\color{#3D99F6}{(a+6)}}{\color{#D61F06}{(a+2)}\color{#3D99F6}{(a+8)}} \times \dfrac{\color{#D61F06}{(a+5)}\color{#3D99F6}{(a+7)}}{\color{#D61F06}{(a+3)}\color{#3D99F6}{(a+9)}} \times ... \right)} \\ = \log_{33} {\left( \dfrac{(a+2)(a+3)}{(a-2)(a-1)} \right)} = 1 \\ \Rightarrow \displaystyle \left(\frac{(a+2)(a+3)}{(a-2)(a-1)} \right) = 33 \\ \quad a^2 + 5a + 6 = 33(a^2-3a+2) \\ \quad a^2 + 5a + 6 = 33a^2-99a+66 \\ \quad 32a^2-104a+60 = 0 \\ \quad 8a^2-26a+15 = 0 \\ \quad (2a-5)(4a-3) = 0 \\ \Rightarrow \begin{cases} a = \frac{5}{2} \\ a = \frac{3}{4} \quad \text{unacceptable, } \ln{(a-1)} \text{ and } \ln{(a-2)} \text{ are undefined} \end{cases}

Therefore, the sum of all possible real values of a a is 5 2 p + q = 5 + 2 = 7 \frac {5}{2} \quad \Rightarrow p+q = 5 + 2 = \boxed{7}

It's not quite enough to say that ln ( a 1 ) \ln(a-1) and ln ( a 2 ) \ln(a-2) are undefined. You need that one of the terms of the sum is undefined, since the log properties you use assume that each log is separately defined. (E.g. ln ( 2 3 ) \ln(-2 \cdot -3) is defined even though ln ( 2 ) \ln(-2) and ln ( 3 ) \ln(-3) are undefined.)

Patrick Corn - 6 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...